The Impact of the flypaper effect on the Province of Bangka Belitung in the Context of Spatial Relationships - Aja Nasrun; Sri Hapsari Murni Handayani (Equity: Jurnal Ekonomi, 2023)
Local governments must ensure proper financial management by carefully planning the allocation of regional funds (such as DAU/DAK/DBH) and expenditures (BELANJA), as well as maximizing effective and efficient income (PAD). However, the funds received by the regions from the central government are being used in an uneven manner, referred to as the flypaper effect. Despite this, the local government's expenditures have failed to close the fiscal gap and the amount of regional funds being used is greater than the amount of regional income. This study trains to examine the presence of the flypaper effect in Bangka Belitung and the impact of spatial elements on it. Utilizing data from 2006 to 2020 and employing a modified row normalized queen contiguity modified matrix with direct transportation connection, the research objectives were deployed. The study utilized the Spatial Durbin Model (SDM) to analyze the data. The findings indicated the presence of the flypaper effect in the Bangka Belitung Islands with spatial dependencies between 2006 and 2020. And only the Decentralized Allocation of Funds (DAU) was affected by the flypaper effect when there was spatial interdependence in Bangka Belitung. The influence of DAU on regional expenditure (BELANJA) was stronger than its effect on regional income (PAD). Increasing BELANJA in one jurisdiction would lead to an increase of 37 percent in other regions. The spillover effect of the decomposed lump-sum grants was related only to DAU in the context of spatial relationship. Local expenditure in Bangka Belitung was dependent on other locals.